The Effect of Capital Expenditure on Financial Performance with Local Revenue as a Mediating Variable - Pramesti, Nuru Nisa; Budi, Raden Budi Hendaris (Dinasti Publisher, 2025)
Abstract: Regional autonomy is an attempt to give local governments more autonomy and less reliance on the federal government. The fact that just a few local governments enjoy this independence, however, is a phenomenon. As a result, this study looks at the variables that may influence regional financial success. Using Local own-source revenue as a mediating variable, this study examines how capital expenditures affect the regional financial performance of East Java Province's cities and districts. The quantitative method is the approach taken. Purposive sampling was utilized to gather data from East Javan district and city administrations' budget reports for 2018–2022. A review of the literature and applicable rules and regulations is the first phase of this investigation. Next comes data collecting, tabulation, analysis, reporting, and publication of the findings. The findings demonstrated that capital expenditure hurt financial performance. Nonetheless, they exerted a beneficial influence on local original revenue, which in turn positively affected financial performance. Economic performance was enhanced by capital investment funded through local original revenue. The study's findings indicate that East Javan districts and cities must increase capital spending and local own-source revenue to enhance their regional financial performance.